2010
DOI: 10.1038/ncomms1014
|View full text |Cite
|
Sign up to set email alerts
|

Deep-sea hydrothermal vent animals seek cool fluids in a highly variable thermal environment

Abstract: The thermal characteristics of an organism ' s environment affect a multitude of parameters, from biochemical to evolutionary processes. Hydrothermal vents on mid-ocean ridges are created when warm hydrothermal fl uids are ejected from the seafl oor and mixed with cold bottom seawater; many animals thrive along these steep temperature and chemical gradients. Twodimensional temperature maps at vent sites have demonstrated order of magnitude thermal changes over centimetre distances and at time intervals from mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
65
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 33 publications
8
65
0
Order By: Relevance
“…The preferred temperature of the gastropods is in the range of 5-13 C based on experiments in pressurized aquaria (Bates et al, 2010), and similar preferences have been observed in in situ experiments (Bates et al, 2005 compared with the gastropods (Bates et al, 2010). While it appears that the palm worms were in areas much cooler than their preferred temperature, we cannot rule out that they aren't aggregated around small jets of warm water that would not have been resolved by our mapping.…”
Section: Environmental Stabilitysupporting
confidence: 66%
See 4 more Smart Citations
“…The preferred temperature of the gastropods is in the range of 5-13 C based on experiments in pressurized aquaria (Bates et al, 2010), and similar preferences have been observed in in situ experiments (Bates et al, 2005 compared with the gastropods (Bates et al, 2010). While it appears that the palm worms were in areas much cooler than their preferred temperature, we cannot rule out that they aren't aggregated around small jets of warm water that would not have been resolved by our mapping.…”
Section: Environmental Stabilitysupporting
confidence: 66%
“…This spike consisted of a rise over 20 hours followed by a decline over the subsequent 200 hours. Maximum temperatures in the arrays went up to 45C which is above the thermal maximum of several of the animal species observed in deployment images (Bates et al, 2010). Across the arrays, the average temperature warmed by 2 C, and 25% of the average increase could be attributed to a single logger.…”
Section: April 2011 Temperature Anomalymentioning
confidence: 75%
See 3 more Smart Citations